Assessment of Protozoa in Oral-Maxillofacial Disorders Regions with or without Cancer therapy and Radiotherapy - Nazhat M.A. Al-Zubaidi (Journal of Global Pharma Technology, 2019)
Cancer therapy and radiotherapy guide to many oral structures disorders consisting of: Harmful feeling, nutrient deficiency due to inability to eat, which increased the infection consequences. The performing study tended to point the protozoa’s frequents Entamoeb gingivalis (E. givg.) and Trichomma Tenax (T.ten.) In patients associated with various oral and maxilla facial pathogeneses regions with or without cancer therapy or radiotherapy, and their correlations with the sex, age of those patients and individuals and how to early control upon these parasitic consequences infections in such patients have these disorders. This study collecting in 205 (100%) individuals, 150 (73.17%) patients with various oral disorders (84 males and 66 females) and 55 (26.82%) UN diseased persons (25 males and 30 females).The two groups range between 15-85 years attended to oral maxillofacial surgery department, in AL Gazy AL Hariri Hospital For Surgical Specialties with various oral cavity disorders and their oral hygiene ranged between gingival, periodontium and oral tissues disorders, most of them under or after cancer chemo therapeutics and radio therapeutic treatment periods or may not receiving yet. Swabs samples were collected by scraping various margins from inside of mouth contain. All samples were held in sterile slides with normal saliva taken to the laboratory of the same hospitals in order to examine and seen under light microscope. Statistically the various clinical cases of oral problems are displayed in this study highly significant in correlation between oral disorders and the frequency of parasites, Improving patients awareness of importance of dental and oral hygiene health before, during and after cancer therapeutic treatment, achieved by making proper oral hygiene instructions programs and minimized the oral disorders complications and their consequence.